Speculative proposals: a design resource for crafting speculative scenarios - Palma, David (2025)
Speculative design is an approach where designers express a set of concerns with sensitive or complex subjects and where they demonstrate ability to develop proposals that detach themselves from the norm, trends or commercial need. However, its stimulation in a professional or teaching context is hampered by its lack of definition or operability. This paper aims to study and examine different speculative design resources for designers, design students, and researchers in understanding, anticipating, and exploring alternative futures. In the end, the results of exploring and prototyping a set of cards and dice are presented, enabling the interpretation and application of more accessible speculative processes for students in the field of Design.